(untitled) (DAPesquisa, 2021)
Based on the HumanizeSUS policy since 2011, the Extension Program on Care and Attention to Children and Teenagers ongoing Onchologic treatment (CAACTO) has developed various activities with children and teenagers affected by neoplasms. To diminish suffering after diagnosis and treatment plus what hospital isolation may cause, weekly musical interventions certainly act as a pleasant interlude and promotes health and human growth. Repeated interventions during 2018 have accomplished the aim of hospital humanization and the construction of an educational space based on music. Music undergraduates enjoy this practice and it enriches the exchange of ideas during CAACTO meetings where theory and practice are discussed in order to search for interdisciplinarity actions and benefits for all involved persons.